Gardening can be murder : how poisonous poppies, sinister shovels, and grim gardens have inspired mystery writers - McDowell, Marta (Timber Press, 2023)
"Plants, borders, and various horticultural paraphernalia make surprisingly frequent appearances in mystery plots. In this wide-ranging survey of classic and contemporary murder fiction, Marta looks at the detectives, motives, methods, opportunities, and writers that have used the garden as their point of departure. The result is a diverting and eye-opening study that deepens our appreciation of the great crime fiction writers while illuminating the close link between murder mysteries and the world of gardening"--